Rehabilitation and Reconstruction Post-Earthquake, Tsunami and Liquefaction Disaster in Central Sulawesi Province - elintia, elintia; Pujo Widodo; Herlina Juni Risma Saragih; Kusuma, Kusuma (CV. AFDIFAL MAJU BERKAH, 2024)
Post-disaster recovery in Central Sulawesi Province covering Sigi District, Donggala District, Parigi Moutong District and Palu City which occurred in 2018 is a national priority program, because the impact is so great. The incident caused damage and losses to various important sectors in people's lives, such as housing, infrastructure, economy, social and cross-sector sectors. Rehabilitation and reconstruction efforts carried out by both central and regional governments and various related parties are certainly needed and have been running for the last 5 years. This study aims to evaluate the efforts that have been made in restoring all affected sectors. The methodology of this study is based on a literature study with the scope of a literature search study through secondary data obtained from where the researcher works, namely BNPB and other sources. The results show that there are 2 areas that have not fully recovered, namely Palu City and Parigi Moutong District. In both areas, there are still sectors that require further attention and action, namely the economic sector in Parigi Moutong District and all sectors in Palu City because they are below the pre-disaster baseline value. Therefore, a sustainable program involving all stakeholders is needed to improve the condition of these sectors.